Republic of Romania : Financial Sector Assessment - World Bank (Washington, DC, 2014)
This financial sector assessment (FSA) summarizes the key findings and recommendations of the 2008 FSAP update report for Romania. The main findings of the FSAP update are: the financial system entered the crisis well capitalized and with high liquidity buffers, and the four financial sector regulatory authorities have made significant progress in adopting international best practice, including through transposition of European Union (EU) directives, and implementation of many of the recommendations of the 2003 FSAP. While the banking system is currently well capitalized, the rapid deterioration in economic conditions and the depreciation of the leu may put strains on bank capital. The measures to strengthen the system are needed: an ex ante strengthening of capital positions is warranted; the overall exposure of foreign parent banks to Romania should be maintained; banks need to develop effective debt restructuring or workout procedures for household and corporate clients; crisis management coordination should be accelerated; bank resolution powers strengthened; and deposit insurance funding and payout arrangements improved. Some cross-sectoral themes emerge to strengthen the supervisory frameworks, including the need to strengthen the political independence and financial autonomy of the non-bank financial regulators; better cross-sectoral cooperation in supervision of financial groups; further movement toward a more risk-based approach to supervision; better consistency in valuation rules for market instruments; adoption of international financial reporting standards (IFRS) accounting; and in the banking sector, strengthening of the basel two implementation framework. Longer term developmental issues include the need to address obstacles to capital market development, certain risks in insurance, and to ensure sustainability of the pension system reform.